Proporsi Kepemilikan Institusional, Beban Pajak Tangguhan, Capital Intensity, dan Manajemen Laba Terhadap Penghindaran Pajak - Mistlu Ladiyana Fidela Latifa; Ratna Herawati; Retno Indah Hernawati; Purwantoro (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to empiricaly prove the infIuence of InstitutionaI Ownership, Deferred Tax Burden, Capital Intensity, Profit Management on Tax Avoidance. The independent variabIes in this study are lnstitutional Ownership (X₁), Deferred Tax Burden (X₂), Capital Intensity (X₃), Profit Management (X₄) and the dependent variabIe is Tax Avoidance (Y). This type of research is quantiitative research and the type of data used is secondary data in the form of financiaI statements of companies in the consumer non-cyclicals sectore that have been pubIished by the IDX (Indonesia Stock Exchange) in 2019-2023. SampIing was conducted using the purposive sampIing method and the population of 129 was obtained which was used as a sample of 29 companies and data processing using the SPSS 26 .